Robust ICP Registration Using Biunique Correspondence - Lei Zhang; Sung-In Choi; Soon-Yong Park (2011 International Conference on 3D Imaging, Modeling, Processing, Visualization and Transmission, 2011)
In this paper, a novel variant of the ICP algorithm is proposed for registration of partially overlapping range images. Biunique correspondence is introduced to enhance the performance of ICP by searching multiple closest points. A new kind of outlier is defined, called No-Correspondence (NC) Outlier, which is the point that is not assigned to a biunique correspondence. In order to maintain efficiency, a coarse-to-fine approach is adopted. Experiments show that the proposed algorithm can find the correct rigid transformation with the existence of large non-overlapping area and poor initial alignment. The proposed algorithm is also applied to SLAM with the use of odometry information.